The GFDL Global Atmospheric Chemistry‐Climate Model AM4.1: Model Description and Simulation Characteristics. (24th October 2020) - Horowitz, Larry W.; Naik, Vaishali; Paulot, Fabien; Ginoux, Paul A.; Dunne, John P.; Mao, Jingqiu; Schnell, Jordan; Chen, Xi; He, Jian; John, Jasmin G.; Lin, Meiyun; Lin, Pu; et al.
Abstract: We describe the baseline model configuration and simulation characteristics of the Geophysical Fluid Dynamics Laboratory (GFDL)'s Atmosphere Model version 4.1 (AM4.1), which builds on developments at GFDL over 2013–2018 for coupled carbon‐chemistry‐climate simulation as part of the sixth phase of the Coupled Model Intercomparison Project. In contrast with GFDL's AM4.0 development effort, which focused on physical and aerosol interactions and which is used as the atmospheric component of CM4.0, AM4.1 focuses on comprehensiveness of Earth system interactions. Key features of this model include doubled horizontal resolution of the atmosphere (~200 to ~100 km) with revised dynamics and physics from GFDL's previous‐generation AM3 atmospheric chemistry‐climate model. AM4.1 features improved representation of atmospheric chemical composition, including aerosol and aerosol precursor emissions, key land‐atmosphere interactions, comprehensive land‐atmosphere‐ocean cycling of dust and iron, and interactive ocean‐atmosphere cycling of reactive nitrogen. AM4.1 provides vast improvements in fidelity over AM3, captures most of AM4.0's baseline simulations characteristics, and notably improves on AM4.0 in the representation of aerosols over the Southern Ocean, India, and China—even with its interactive chemistry representation—and in its manifestation of sudden stratospheric warmings in the coldest months. Distributions of reactive nitrogen and sulfur species, carbon monoxide, and ozone are all substantially improved over AM3. Fidelity concerns include degradation of upper atmosphere equatorial winds and of aerosols in some regions. Plain Language Summary: GFDL has developed a coupled chemistry‐climate Atmospheric Model (AM4.1) as part of its fourth‐generation coupled model development activities. AM4.1 includes comprehensive atmospheric chemistry for representing ozone and aerosols and has been developed for use in chemistry and air quality applications, including advanced land‐atmosphere‐ocean coupling. With fidelity near to that of AM4.0, AM4.1 features vastly improved representation of climate mean patterns and variability from previous GFDL atmospheric chemistry‐climate models. Key Points: A new atmospheric chemistry‐climate model (AM4.1) has been developed for the Geophysical Fluid Dynamics Laboratory (GFDL)'s fourth‐generation model suite AM4.1 includes an advanced dynamical core and physical parameterizations, with enhanced vertical resolution and revised aerosol and chemistry interactions The AM4.1 model exhibits substantially enhanced fidelity compared to previous‐generation GFDL atmospheric models